Unraveling the deadly dance: endothelial cells and neutrophils in sepsis-induced acute lung injury/acute respiratory distress syndrome - Xu, Xiujuan; Zhang, Qi; Lv, Zheng; Cheng, Chuji; Zha, Junjing; Shu, Huaqing; Xiao, Hairong; Pan, Shangwen (Frontiers in Cell and Developmental Biology, 2025)
Sepsis-induced acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are severe complications with high morbidity and mortality rates, characterized primarily by diffuse alveolar damage, endothelial dysfunction, and local inflammatory responses. Neutrophils and endothelial cells (ECs) play crucial roles in the pathogenesis and progression of these diseases. Neutrophils are important regulators of inflammation, while endothelial dysfunction exacerbates vascular permeability and the inflammatory cascade. The interaction between neutrophils and ECs is vital for the development of ALI/ARDS induced by sepsis, driving the pathological processes of inflammation and tissue damage. Despite advancements in treatment strategies such as protective mechanical ventilation and fluid management, effective methods for rapid lung tissue recovery or significant improvement in outcomes remain lacking. Therefore, we comprehensively summarize the current literature to gain deeper insights into the roles of neutrophils, ECs, and their interactions in sepsis-induced ALI/ARDS, hoping to provide critical insights into the mechanisms underlying sepsis-related ALI/ARDS and potential pathways for developing new therapeutic approaches.